1996
DOI: 10.1093/oxfordjournals.jbchem.a021396
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Seed Oil Bodies and Their Surface Oleosin Isoforms from Rice Embryos

Abstract: Plant seeds store triacylglycerols in discrete organelles called oil bodies. An oil body stores a matrix of triacylglycerols surrounded by phospholipids and alkaline proteins termed oleosins. Oil bodies in rice seeds are present in embryos and aleurone layers. They do not coalesce in crowded environments, as observed on electron microscopy. The detected isoelectric point of purified rice oil bodies is pH 6.2. This implies that rice oil bodies possess a negatively charged surface at neutral pH. The suspension o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
4
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 0 publications
2
32
4
1
Order By: Relevance
“…In several species, the diŠerence in molecular mass between H-oleosin and L-oleosin is 2 kDa: maize has 18-and 16-kDa oleosins; 8) Arabidopsis thaliana has 21-and 19-kDa oleosins; 24,25) barley has 18-and 16-kDa oleosins; 26) rice has 18-and 16-kDa oleosins; 27) and sesame has 17-and 15-kDa oleosins (this report). Presumably, the diŠerence is constant because of the insertion of 18 residues (¿2 kDa) in the C-terminal domain of the H-oleosins.…”
Section: Classiˆcation Of Sesame Oleosin Isoformsmentioning
confidence: 76%
“…In several species, the diŠerence in molecular mass between H-oleosin and L-oleosin is 2 kDa: maize has 18-and 16-kDa oleosins; 8) Arabidopsis thaliana has 21-and 19-kDa oleosins; 24,25) barley has 18-and 16-kDa oleosins; 26) rice has 18-and 16-kDa oleosins; 27) and sesame has 17-and 15-kDa oleosins (this report). Presumably, the diŠerence is constant because of the insertion of 18 residues (¿2 kDa) in the C-terminal domain of the H-oleosins.…”
Section: Classiˆcation Of Sesame Oleosin Isoformsmentioning
confidence: 76%
“…Right after the kick-off studies on maize oleosins, homologous oleosin isoforms were subsequently identified in oil bodies of rapeseed (Brassica napus), soybean (Glycine max L.), carrot (Daucus carota), sunflower (Helianthus annuus), Arabidopsis thaliana, and cotton (Gossypium hirsutum) with their corresponding cDNA fragments cloned [27][28][29][30][31][32][33][34]. It seems that oleosin isoforms are universally present in oil bodies of angiosperm seeds including both monocotyledonous and dicotyledonous species [35][36][37][38][39]. Furthermore, oleosin isoforms found as the major proteins (approximately 80-90%) in seed oil bodies were demonstrated to shield the whole surface of the organelles in the company of phospholipids [40].…”
Section: Identification Of a Major Integral Protein In Seed Oilmentioning
confidence: 99%
“…The central long hydrophobic core has a unique proline knot, PX 5 SPX 3 P, that is conserved across various species and is used for targeting the protein to oleosomes (9, 10) but is not required for integration into the membrane of the endoplasmic reticulum. A mutation in the conserved residues of the proline knot resulted in inefficient targeting to the oil body; however, oleosin maintained its normal level in seeds (11,12). Oleosins are not only restricted to oil bodies but are also expressed specifically in the floral tapetum cells of the pollen tube in Arabidopsis (13).…”
Section: Triacylglycerol (Tag)mentioning
confidence: 99%
“…The extract was filtered through two layers of cheesecloth, and the filtrate was differentially centrifuged to fractionate the intracellular components. The oleosomes were prepared as described previously (12).…”
Section: Triacylglycerol (Tag)mentioning
confidence: 99%